2010
DOI: 10.1093/rheumatology/keq271
|View full text |Cite
|
Sign up to set email alerts
|

Increased cysteinyl-leukotrienes and 8-isoprostane in exhaled breath condensate from systemic sclerosis patients

Abstract: Increased levels of CysLT and 8-isoprostane in EBC from patients with SSc reflect the inflammatory pattern involving LTs as well as oxidative stress. These findings may indicate a possible non-invasive assessment of pulmonary involvement in SSc with a potential value for assessment of disease progress and therapy evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Although the concentration of LTB4 significantly correlated with the concentration of cysteinyl leukotrienes, the difference in LTB4 levels was not significant between SSc patients and the control group. No association was documented in this group between the leukotriene concentrations and radiological findings of HRCT or functional pulmonary tests [25]. There is no ready explanation for the discrepancies between measurements of www.fhc.viamedica.pl LTB4 in BALF and exhaled breath condensates; however, it could be due to the limited numbers of patients with SSc-ILD in the study by Tufvesson and/or the influence of treatment which could potentially alter leukotriene metabolism.…”
Section: Leukotrienes and Systemic Sclerosismentioning
confidence: 68%
See 1 more Smart Citation
“…Although the concentration of LTB4 significantly correlated with the concentration of cysteinyl leukotrienes, the difference in LTB4 levels was not significant between SSc patients and the control group. No association was documented in this group between the leukotriene concentrations and radiological findings of HRCT or functional pulmonary tests [25]. There is no ready explanation for the discrepancies between measurements of www.fhc.viamedica.pl LTB4 in BALF and exhaled breath condensates; however, it could be due to the limited numbers of patients with SSc-ILD in the study by Tufvesson and/or the influence of treatment which could potentially alter leukotriene metabolism.…”
Section: Leukotrienes and Systemic Sclerosismentioning
confidence: 68%
“…Recently, Tufvesson et al measured the concentration of leukotrienes in exhaled breath condensates of 22 patients with SSc, including 12 patients with SSc-ILD as defined by the presence of traction bronchiectasis within areas of ground-glass opacities and/ /or reticulation in high resolution computed tomography (HRCT) of the lungs [25]. They showed that concentration of cysteinyl leukotrienes is significantly higher in exhaled breath condensates of SSc patients compared to healthy controls.…”
Section: Leukotrienes and Systemic Sclerosismentioning
confidence: 99%
“…There appear to be diseases where the 5-lipoxygenase pathway is constitutively activated and LTs are produced constantly, as in idiopathic pulmonary fibrosis 2) and systemic sclerosis 3) . LTs are involved in the pathogenesis of lung fibrosis by direct effects on migration, proliferation and matrix protein synthesis by fibroblasts, as well as by indirect effects, such as suppression of the production of antifibrogenic cytokines 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increased urinary levels of 8-isoprostanes were previously found in SSc patients in the early stages of the disease (Cracowski et al, 2001). It has also been reported that 8-isoprostane in exhaled breath condensate of SSc patients is increased (Tufvesson et al, 2010). Similarly, it was demonstrated that bronchoalveolar lavage fuid from SSc patients with fibrosing alveolitis contained increased levels of 8-isoprostanes (Montuschi et al, 1998).…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 93%